Microbiological Quality of Street Vended Drinking Water in Dhaka City and Screening for Antibiotics Resistance of Isolated Salmonella spp and Pseudomonas spp. - Ahmed, S.; Mahbub, K. R.; Ahmed, M. M.; Rahman, M.; Hoque, M. M. (Journal of Scientific Research, 2014)
<!--[if gte mso 9]> <![endif]--> The present study was aimed to assess the microbiological quality of street vended drinking water of Dhaka city. The water samples were collected from street vendors in different areas of Dhaka city. All of the 30 samples were found having microorganisms higher than WHO limits for drinking water. Four (13.34%) samples were confirmed to have Salmonella contamination and twenty (66.67%) samples were contaminated with Pseudomonas. Based on morphological and biochemical characterization Salmonella isolates were identified as Salmonella choleraesuis and Salmonella bongori. Among the isolates of Pseudomonas, fourteen were identified as Pseudomonas alcaligens and six were as Pseudomonas aeruginosa. During antibiogram for Salmonella, 100% of the isolates were found resistant to Penicillin. Chloramphenicol, doxycycline, Gentamycin, Neomycin were sensitive to all of the isolates. The Pseudomonas isolates showed a significant drug resistance to Penicillin (100%), Ampicillin (95%), Amoxicillin (95%) and Nalidixic acid (85%). The present study demonstrates that drinking water samples from street vendors in Dhaka city are not complying with microbiological specifications of WHO and indicates that street vending drinking water in Dhaka city may not be safe for human consumption and also shows that these are the potential sources of drug resistance Salmonella and Pseudomonas. Keywords: Street vended drinking water; Antibiotic resistance; Salmonella; Pseudomonas. © 2014 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v6i2.17640 J. Sci. Res. 6 (2), 359-371 (2014) <!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin:0cm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->